2017
DOI: 10.1080/15548627.2017.1327104
|View full text |Cite
|
Sign up to set email alerts
|

An iron hand over cancer stem cells

Abstract: The paradigm of cancer stem cells (CSCs) defines the existence of cells exhibiting self-renewal and tumor-seeding capacity. These cells have been associated with tumor relapse and are typically resistant to conventional chemotherapeutic agents. Over the past decade, chemical biology studies have revealed a significant number of small molecules able to alter the proliferation of these cells in various settings. The natural product salinomycin has emerged as the most promising anti-CSC agent. However, an explici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Accordingly, in a very recent paper 56 , it has been reported a pronounced effect of ironomycin, an inducer of ferroptosis, against CSCs derived from breast human mammary epithelial cells. These findings could directly implicate that iron homeostasis could represent a key regulator of the survival or death of CSCs 57 . Accordingly, in GSCs we detected an activation of cathepsin B that may be due to lysosome membrane permeabilization, lipid peroxidation, and decreased endogenous levels of the reduced form of glutathione, which is consistent with the induction of ferroptotic cell death.…”
Section: Discussionmentioning
confidence: 91%
“…Accordingly, in a very recent paper 56 , it has been reported a pronounced effect of ironomycin, an inducer of ferroptosis, against CSCs derived from breast human mammary epithelial cells. These findings could directly implicate that iron homeostasis could represent a key regulator of the survival or death of CSCs 57 . Accordingly, in GSCs we detected an activation of cathepsin B that may be due to lysosome membrane permeabilization, lipid peroxidation, and decreased endogenous levels of the reduced form of glutathione, which is consistent with the induction of ferroptotic cell death.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, a new type of programmed cell death, ferroptosis, is also closely related to Fe 2+ and the Fenton reaction[ 177 ]. Some researchers have found that ferricin chelates lysosomal iron[ 178 ]. These compounds induce iron depletion by preventing iron transport, leading to the dissolution of ferritin.…”
Section: Impact Of Ros From Pdt On Cscsmentioning
confidence: 99%
“…In human H460 and H292 NSCLC cells, the subchronic exposure to ironinduced oxidative stress leads to a remarkable increase in CSC spheroids in parallel with an increase in ABCG2 CSC marker [60]. Accordingly, Hamai, et al demonstrate that iron-depletion, followed by an overproduction of ROS, promotes cancer stem cell death [61]. In SKOV3 epithelial ovarian cancer cells, low FHC levels promote cancer stem cell spheroids accumulation along with the increase in stemness markers expression most likely through an iron-independent mechanism involving the regulation of miR-150 and miR-146a [34].…”
Section: Ferritin and Cancer Stem Cellsmentioning
confidence: 99%